Young Adults' Reactions and Engagement with Short-form Videos on Sea Level Rise. Issue 1 (2nd January 2022) - Shriver-Rice, Meryl; Fernandes, Juliana; Johns, Lisa N.; Riopelle, Cameron; Vaughan, Hunter
ABSTRACT: This study examines young South Floridians' perceptions of visual elements and four generic types of engagement identified via a novel interdisciplinary methodology (Vaughan, H., & Johns, L. N. [2021]. Beyond frame analysis: Formal analysis and genre typology in the communication study of short-form environmental video messaging. Journal of Environmental Media, 2 (1), 55–78. https://doi.org/10.1386/jem_00040_1) combining formal analysis and genre theory in short-form videos on sea-level rise. We employ a mixed-methods approach in order to examine how formal aspects, such as the use of direct address, voiceover, computer animation and digital simulation, narrative structure, and musical score impact viewer reception of 10 short-form videos and sharing behavior. An inductive analysis of emergent themes identifies several notable aspects that should be considered by practitioners of environmental media in the design and execution of compelling and persuasive short-form videos. Key results point to the importance of focusing on human stories and voices, a narratology that emphasizes practical actions and solutions, a measured use of humor and overly evocative musical scores, as well as the importance of video source and overall quality.